FPCB STIFFENER ADHESIVE MACHINE DYNAMIC PERFORMANCE OPTIMIZATION AND ACCURACY ANALYSIS - MEI LingLiang; LIN XiaoXia; MEI XueSong (Jixie qiangdu)
Aiming at the problem of the FPCB（ flexible printed circuit board） stiffener adhesive machine performance optimization,applying the finite element method,a FEA model of the FPCB stiffener adhesive machine has been set up. The stiffness and modal analysis of the current structure have been done. According to simulation results,there was a large deformation at the marble platform. The first and second inherence frequencies of the structure were rather low. Therefore,do the optimization and improvement design to strengthen this structure. After improvement design,the stiffness and each natural frequency of this machine have improved a lot. The experiment testing shows that,the stability and the position accuracy of this machine have improved a lot after improvement design.